2011
DOI: 10.1063/1.3590921
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Poissonian shot noise in CoFeB/MgO/CoFeB-based magnetic tunneling junctions

Abstract: We measured the shot noise in the CoFeB/MgO/CoFeB-based magnetic tunneling junctions with a high tunneling magnetoresistance ratio (over 200 % at 3 K). Although the Fano factor in the anti-parallel configuration is close to unity, it is observed to be typically 0.91±0.01 in the parallel configuration. It indicates the sub-Poissonian process of the electron tunneling in the parallel configuration due to the relevance of the spin-dependent coherent transport in the low bias regime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 22 publications
5
37
0
Order By: Relevance
“…The recently discovered spin Seebeck effect [10] is attributed to an imbalance of spin-current fluctuations [11,12] caused by a thermal gradient in a ferromagnet|normal metal bilayer system. Spin-dependent coherent transport could be detected in magnetic tunneling junctions (MTJs) via current shot-noise measurements [13,14]. However, a direct measurement of thermal spin-current noise has, to our knowledge, not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…The recently discovered spin Seebeck effect [10] is attributed to an imbalance of spin-current fluctuations [11,12] caused by a thermal gradient in a ferromagnet|normal metal bilayer system. Spin-dependent coherent transport could be detected in magnetic tunneling junctions (MTJs) via current shot-noise measurements [13,14]. However, a direct measurement of thermal spin-current noise has, to our knowledge, not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…(21) and (23), and substituting them into Eq. (18), one arrives at the following relation between the total current fluctuation and its Langevin part:…”
Section: Shot Noise In the Presence Of Spin Relaxationmentioning
confidence: 99%
“…14,15 It has also been shown experimentally that the Fano factor in a single-barrier magnetic tunnel junction depends on magnetic configuration of the junction, and can be remarkably enhanced for the antiparallel alignment of the electrodes' magnetizations. [16][17][18][19][20] Even more possibilities have been found in double-barrier tunnel junctions with two ferromagnetic electrodes and one ferromagnetic central layer, 21,22 where one can distinguish four magnetic configurations corresponding to different alignments of the magnetic moments of all three magnetic layers. 23 It has also been shown that a simple model based on two well-separated spin channels for electronic transport cannot properly describe the experimental observations without taking into account spin-flip transitions.…”
Section: Introductionmentioning
confidence: 99%
“…49,[53][54][55] The cross-correlation technique is employed as shown in Fig. 3(a) to minimize the external noise from the cables and the amplifiers.…”
Section: High-frequency Measurementsmentioning
confidence: 99%